Factors Affecting Dividend Payment Decisions: The Case of Libya - BUDAGAGA, AKRAM (Archives of Business Research, 2018)
This research paper will investigate the views of executives and top management of firms listed on the Libyan Stock Market [LSM] regarding the main factors affecting dividend payment decisions. A questionnaire has been used to gather primary data from a range of industries. The evidence reports that the most influential factors in making dividend payment decisions involve: earnings [level of current earnings], Patterns of past dividends, investment opportunities, and liquidity [availability of cash]. Furthermore, the viewpoints of the respondents from three industry sets show no difference in the importance of the dividend factors among industries groups, except the level of reserve.Therefore, the industry type issue appeared to influence the importance that respondents placed on determinants of dividend payment decisions. The findings also show that respondents strongly believe that dividend payment is an important issue in Libyan firms, and these results are consistent with signaling and Pecking order explanations for paying cash dividends.